Reliability of diaphragmatic mobility assessment using a real time ultrasound among non-specific low back pain - Vikram Mohan (2018)
© 2017, Ibn Sina Trust. All rights reserved. Background and Objective: Ultrasound measurement of Diaphragmatic Mobility (DM) has been shown to be a reliable measurement tool among healthy subjects. However, the measures of reliability are needed prior to clinical use of this device among Non-Specific Low Back Pain (NS-LBP). Therefore, the aim of the study was to investigate the relative and absolute reliability of DM using Real Time Ultrasound (RTUS) among subjects with NS-LBP. Materials and Methods: Nine subjects with NS-LBP (23.33 ± 1.58) years old were recruited. A qualified examiner performed measurement of DM using RTUS by placing transducer on the right subcostal region in semi-fowler’s position with 30 degree elevation of the trunk. The test-retest measures were re-assessed with 24 hour interval between sessions. Results: There was no systematic errors between the test-retest measures (p > 0.05). Intra rater reliability showed ICC value of 0.92, which indicates an excellent reliability. The SEMs of the measurement was 2.56 mm and the MDC of 7.09mm. Conclusion:The RTUS for assessing DM provides an excellent intra-rater reliability which may be used as an assessment technique for clinical evaluation of DM in adults with NS-LBP. The SEMs and MDC reported may also allow for accurate interpretation of DM assessments in NS-LBP.